THU0578 Spectrum of the diseases with orbital involvement in rheumatology: single-center study. (15th June 2017) - Vasilyev, V; Gorodetskiy, V; Safonova, T; Probatova, N; Kokosadze, N; Pavlovskaya, A; Kovrigina, A; Gaiduk, I
Abstract : Background: It is assumed that in ophthalmological clinical practice lymphoproliferative disorders in patients with affection of different orbital organs and tissues constitute 25–55% and 21% of patients have IgG4-related ophthalmic disease [1, 2]. Objectives: To evaluate the most common conditions affecting the orbit in rheumatologic clinical practice. Methods: During 2004 – 2016 years 138 patients (male – 33, female - 105) with eyelid edema and/or tumefactive lesions in the orbit were examined in Nasonova Research Institute of Rheumatology. In all patients full clinical, ophthalmological, serological (rheumatoid factor, C-reactive protein, IgG, IgG4, IgM, IgA, ANA, anti-Ro/La, C3/C4 complement) examination was carried. In all cases diagnosis was verified pathomorphologicaly with immunohystochemical staining (anti-CD 138, CD 68, IgG, IgG4, κ-chain, λ-chain). Diagnosis was established on the basis of pathomorphological examination of different tissues: orbit – 79 patients, parotid salivary gland – 40, submandibular salivary gland – 14, nasal – 4, lymph nodes – 3 and other – 6. In 79 cases (54%) the diagnosis was established on the results of orbital biopsy. Results: Different non-neoplastic diseases were diagnosed in 108 patients (78.5%) and 30 had different conditions of hematological spectrum, including malignant conditions in 25 (18.2%) patients (see table 1 ). Some patients at baseline had simultaneous involvement of the major salivary glands (23 patients with IgG4-related disease, 35 with sarcoidosis, 12 with non-Hodgkin lymphomas and 2 with AL-amyloidosis). The most rare conditions affecting the orbit were Cogan's syndrome, relapsing polychondritis, Erdheim-Chester disease, NK/T-cell nasal lymphoma and calcifying aponeurotic fibroma. Conclusions: In rheumatologic practice in 78.5% of patients with orbital involvement different non-neoplastic conditions are diagnosed: IgG4-related ophthalmic disease (35.0%), granulematous lesions (29%). The most common hematological disorders in rheumatologic clinic are non-Hodgkin lymphomas (17.5%) and histiocytosis (3.5%). References: Japanese study group of IgG4-related ophthalmic desease. A prevalence study 0f IgG4-related ophthalmic disease in Japan.JpnJOphthalmol.2013;57: 573–579. Shields JA et al. Survey of 1264 patients with orbital tumors and simulating lesions: the 2002 Montgomery Lecture, part I. Ophthalmology.2004;111: 997–1008. Goto H et al. Diagnostic criteria for IgG4-related ophthalmic disease. JpnJOphthalmol.2015;59:1–7. Disclosure of Interest: None declared